HOW TO PRODUCE VIDEO LECTURES TO ENGAGE STUDENTS AND DELIVER THE MAXIMUM AMOUNT OF INFORMATION - Alksne, Linda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
This paper is dedicated to the analysis of literature about video lectures and finding out the conditions and rules for planning and delivering a good video lecture for modern learning. Different publications and materials on the design and delivery experience of video lectures in learning situations have been analysed. The presented set of the design and delivery experience data of video lectures could be used to create more efficient methods of improving the instruction quality of video lectures.